2019
DOI: 10.1080/10400435.2019.1581303
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’, teachers’, and assistants’ use and learning of partner strategies in communication using high-tech speech-generating devices with children with severe cerebral palsy

Abstract: Sonnander (2019): Caregivers', teachers', and assistants' use and learning of partner strategies in communication using high-tech speech-generating devices with children with severe cerebral palsy, Assistive Technology,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…Research found that social and pedagogical inclusion of students with, for example, complex communication needs was demanding (Andzik et al, 2016;Radford et al, 2015;T€ onsing & Dada, 2016). Moreover, implementing eye-gaze accessed SGDs in classroom settings was difficult (Rytterstr€ om, Borgestig, & Hemmingsson, 2016;Tegler, Pless, Blom Johansson, & Sonnander, 2019;van Niekerk & T€ onsing, 2015). In a study by Rytterstr€ om et al (2016), teachers expressed a conflict between the need to follow the process on the SGD screen, the student's eye movements and facial expressions, and the need to face the rest of the class.…”
mentioning
confidence: 99%
“…Research found that social and pedagogical inclusion of students with, for example, complex communication needs was demanding (Andzik et al, 2016;Radford et al, 2015;T€ onsing & Dada, 2016). Moreover, implementing eye-gaze accessed SGDs in classroom settings was difficult (Rytterstr€ om, Borgestig, & Hemmingsson, 2016;Tegler, Pless, Blom Johansson, & Sonnander, 2019;van Niekerk & T€ onsing, 2015). In a study by Rytterstr€ om et al (2016), teachers expressed a conflict between the need to follow the process on the SGD screen, the student's eye movements and facial expressions, and the need to face the rest of the class.…”
mentioning
confidence: 99%